Stock Market Development and Environmental Sustainability in Saudi Arabia: Asymmetry Analysis - Adow, Anass Hamadelneel (International Journal of Energy Economics and Policy, 2024)
Stock Market Development (SMD) can have positive or negative environmental effects by providing the capital to clean or dirty production processes, respectively. The present study investigates the effect of SMD on CO2 emissions in Saudi Arabia from 1985 to 2022 by conducting symmetrical and asymmetrical analyses. The results validate the environmental Kuznets curve in both symmetrical and asymmetrical analyses. The turning point of the curve is found at 61500 SR and 49944 of income per capita in symmetrical and asymmetrical analyses, respectively, in the long run. The turning points are found at 65895 SR and 54979 SR in the symmetrical and asymmetrical models, respectively, in the short run. All points are within the range of sample period’s income. Thus, Saudi economic growth has no environmental problems. Moreover, SMD and increasing SMD help reduce CO2 emissions in the long run with elasticity parameters 0.8548 and 0.9854 in symmetrical and asymmetrical models, respectively. Thus, SMD should further be focused to have pleasant environmental effects in Saudi Arabia.